Juvenile rheumatoid arthritis presented with thrombocytopenia - Koç, Ahmet; Kösecik, Mustafa; Tatlı, M. Mansur; Ataş, Ali; Emiroğlu, H. Haldun (The Turkish Journal of Pediatrics, 2000)
Leukopenia and thrombocytopenia are rare findings in systemic onset juvenile rheumatoid arthritis (S-JRA), and if present, bone marrow (BM) examination is necessary to exclude malignant diseases. We report here a 13.5-year-old boy with S-JRA who had severe thrombocytopenia and mild leukopenia, without arthritis, at the onset of the disease. BM was hypercellular with increased numbers of myeloid precursors and megakaryocytes. After treatment with acetylsalicylic acid, leukocyte and platelet counts returned to normal levels, and after two months chronic arthritis developed.
Keywords: systemic onset juvenile rheumatoid arthritis; thrombocytopenia; fever